Narasi Mitos Lembu Suro dalam Cerpen Janji Kelud untuk Bapak Karya M. Rosyid H. W. - Mulyaningtyas, Rahmawati; Putri, Nuraini Saura; Arinugroho, Yogi Dian (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The short story is a reflection of the reality of human life. The short story entitled Janji Kelud untuk Bapak is interesting to review because it includes the myth of the appearance of Lembu Suro when Mount Kelud erupts. This myth is believed by the people around Mount Kelud that when the mountain erupts, it is as a sign that Lembu Suro comes out and takes a revenge for the injustice he has experienced. This research aims to elaborate the mythical narration of Lembu Suro in the short story of Janji Kelud untuk Bapak. This research uses a mythopoeic approach. Then, Claude Levi-Strauss’ structuralism theory is applied to analyze the myth of Lembu Suro in the short story. The research method uses descriptive qualitative. The main source of this research is a short story entitled Janji Kelud untuk Bapak by M. Rosyid H.W. Data collection is done by reading and writing technique. Data analysis is carried out by sorting and selecting data in the form of narrative sentences or dialogues of characters that are in accordance with the research objectives, then analyzing the data according to the theory used in the research. Checking the validity of the data is applied by reading the data collection and analyzing data repeatedly, then connecting it to the theory. The results show that the myth of Lembu Suro who is at the base of Mount Kelud and will come out when the mountain erupts can be related to the following things, namely (1) belief in something; (2) the behavior patterns of the residents; (3) the impact of the event on the environment around the mountain and the country. The myth of Lembu Suro has been shown and emphasized in a short story entitled Kelud’s Promise for Father. This research is useful to make any contribution in the analysis of myths in literary works.